2018
DOI: 10.1145/3186316
|View full text |Cite
|
Sign up to set email alerts
|

On Automated Memoization in the Field of Simulation Parameter Studies

Abstract: Processes in computer simulations tend to be highly repetitive. In particular, parameter studies further exasperate the situation as the same model is repeatedly executed with only partially varying parameters. Consequently, computer simulations perform identical computations, with identical code, identical input, and hence identical output. These redundant computations waste significant amounts of time and energy. Memoization, dating back to 1968, enables the caching of such identical intermediate r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…We also explore the memoization method [34] to further speed up the simulation. Memoization enables the simulator to cache results of selected expensive functions.…”
Section: Simulation Performance Enhancementmentioning
confidence: 99%
“…We also explore the memoization method [34] to further speed up the simulation. Memoization enables the simulator to cache results of selected expensive functions.…”
Section: Simulation Performance Enhancementmentioning
confidence: 99%
“…Furthermore, the simulation of a quantum network involves repeated computation of this matrix multiplication. Therefore, we utilize the memoization technique [41] to…”
Section: Local Quantum State Managermentioning
confidence: 99%
“…In the first article (Stoffers et al 2018), an automated memoization approach is shown to speed up simulations done as part of an overall parameter study by avoiding redundant computations. What make this approach most interesting is the support of impure functions such as C++ code blocks that perform complex pointers accesses to read object data values.…”
Section: Guest Editorial For the Tomacs Special Issue On The Principlmentioning
confidence: 99%